Optimal Inattention to the Stock Market - Abel, Andrew B; Eberly, Janice C; Panageas, Stavros (American Economic Review, 2007)
Inattentive agents update their information sporadically, and thus respond belatedly to news. We generate optimally inattentive behavior by assuming that to observe the value of his investment portfolio the consumer must pay a cost that is proportional to the portfolio’s contempo raneous value. It is optimal for the consumer to check his investment portfolio at equally spaced points in time, consuming from a riskless trans actions account in the interim. The riskless transactions account that finances consump tion guarantees that funds are never unwittingly exhausted. We show that the optimal interval of time between consecutive observations of the value of the portfolio is the unique positive solution to a nonlinear equation. Quantitatively, even a small observation cost (one basis point of wealth) implies a substantial (eight-month) decision interval under conventional parameter values.